The relationship between preterm and small for gestational age on child cognition during school-age years - Nguyen, Phuong Thi; Nguyen, Phuong Hong; Tran, Lan M.; Khuong, Long K.; Nguyen, Son V.; Young, Melissa F.; DiGirolamo, Ann; Ramakrishnan, Usha (Elsevier, 2024)
Objectives: Children born preterm and/or small for gestational age (SGA) have a high susceptibility to neurological impairments that may affect cognitive and learning outcomes during school age and beyond. Yet, limited evidence exists for these high-risk birth phenotypes in low and middle-income countries where most occur with different etiology and socio-biology. This paper examined the deficits in cognitive function and academic achievement during the school age years in children born preterm or SGA compared to term adequate for gestational age (AGA) in rural Vietnam.